In vitro assay of factors affecting the growth of pathogens associated with diseases on dragon fruits (Hylocereus spp.) in Peninsular Malaysia. - Masyahit, M; Sijam, Kamaruzaman; Awang, Yahya; Satar, M. G. M (Asian Network for Scientific Information, 2009)
Knowing the unfavorable environment for the growth of a pathogen can be utilized as the basic information in developing appropriate strategies to prevent disease occurrence on dragon fruit. Several environmental factors including temperature, pH and salinity, as well as biotic factor including three antagonistic bacteria species, namely Bukholderia cepacia, B. multivorans and Pseudomonas aeruginosa against Bipolaris sp., Colletotrichum gloeosporioides, Botryosphaeria sp. and Monilinia sp., were investigated. Mycelial growth of all tested fungi was constantly inhibited by a temperature of 35°C, while a temperature of 25°C was quite suitable for their growth. A temperature of 30°C was favorable for the growth of Colletotrichum gloeosporioides. Under different pH condition, the growth of tested fungi was mostly inhibited by extreme pH of 4 and 10. The salinity assay showed that Monilinia sp. was not affected by all treatments among tested fungi. Only concentration 100 ppm could reduce the growth of Bipolaris sp., though its inhibition statistically affected on 4 and 6 Days after Incubation (DAI). Meanwhile, the in vitro examination of antagonistic bacteria resulted in Bukholderia multivorans which was highly effective in inhibiting the growth of examined fungi, except Monilinia sp., which was more significantly influenced by B. multivorans and B. cepacia. The proper combination of environmental modification may be useful for the growth of crop in the field as well as the storage life of the fruit at postharvest preservation.